Real-Time Hybrid Simulation Analysis of Moat Impacts in a Base-Isolated Structure - Harris, Michael J.; Christenson, Richard E. (Frontiers in Built Environment, 2020)
Base isolation is a well-known technique used to reduce accelerations and inertial forces in structures during earthquakes. However, excessive displacements of the structure due to flexibility of the isolation layer bearings may contribute to moat wall impact events. These impact events have the potential to cause substantial structural damage. This impact behavior and the effects on structural dynamics have been shown to be highly complex and difficult to model by means of pure numerical simulation. In this paper, the cyber-physical technique called Real-Time Hybrid Simulation (RTHS) is employed to capture the uncertainties in force profiles of moat wall impacts and to analyze the complex interactions between impacts and the dynamics of base-isolated structures during earthquake excitations. It is shown that RTHS is capable of accurately capturing the interactions between the isolation layer and moat wall during impact events induced by ground motions. In addition, the RTHS technique is used to analyze the role played by moat wall material nonlinearities in reducing the inertial demand on the structure during impact events. Finally, possible extensions of the research to larger scales as well as consideration of additional moat wall variants are proposed.